Association between gestational age at delivery and indicator-specific severe maternal morbidity. (31st December 2023) - Phillips, Jaclyn M.; Bodnar, Lisa M.; Himes, Katherine P.
Abstract: Objective: Individuals who deliver preterm are disproportionately affected by severe maternal morbidity. Limited data suggest that indicator-specific maternal morbidity varies by gestational age at delivery. We sought to evaluate the relationship between gestational age at delivery and the incidence of severe maternal morbidity and indicator-specific severe maternal morbidity. Methods: We used a hospital administrative delivery database to identify all singleton deliveries between 16 and 42 weeks gestation from 2002 to 2018. We defined severe maternal morbidity as the presence of any International Classification of Disease diagnosis or procedure codes outlined by the Centers for Disease Control and Prevention, intensive care unit admission, and/or prolonged postpartum hospital length of stay. Indicator-specific severe maternal morbidity was based on the diagnosis and procedure codes and was characterized across gestational age epochs. We categorized gestational age into three epochs to capture extremely preterm birth (less than 28 weeks gestation), preterm birth (28-36 weeks gestation) and term birth (37 weeks gestation and above). Multivariable binomial regression was used to assess the association between categories of gestational age at delivery and severe maternal morbidity adjusting for confounders including age, race, body mass index (BMI), insurance status, and preexisting hypertension or diabetes. Results: Severe maternal morbidity occurred in 2.5% of all deliveries. The unadjusted incidence of severe maternal morbidity by gestational age epoch was 12% at less than 28 weeks gestation, 8.4% at 28 to 36 weeks of gestation, and 1.7% at greater than or equal to 37 weeks gestation. After controlling for potential confounders the predicted probability of severe maternal morbidity was 16% (95% CI 14, 17%) at 24 weeks compared to 2.2% (95% CI 2.1, 2.3%) at 38 weeks. Sepsis, acute respiratory distress syndrome, mechanical ventilation, and shock were the most common diagnostic codes in deliveries less than 28 weeks gestation. Heart failure and cardiac arrhythmias were more common in patients with severe maternal morbidity delivering at term. Conclusion: A high proportion of severe maternal morbidity occurred in preterm patients, with the highest rates occurring at less than 28 weeks gestation. Individuals with severe maternal morbidity who deliver preterm had distinct indicators of morbidity compared to those who deliver at term.